COLLECTING & DISSEMINATING COVID-19 DATA - FROM FRUSTRATION TO FRUITION - Nausheen Bakht (Army Medical College Rawalpindi, 2020)
In the unprecedented COVID-19 situation, Medical Directorate needed to get near-real-time data for decision making and policy formulation. Crisis Management Cell was hence established with a vision to act as a data collection point and repository for Armed Forces COVID-19 PCR positive cases. Its foremost task was transforming a traditionally passive system for disease surveillance to a near-real-time semi-automated one. This coupled with the ensuing workload in the coming days especially during surge, constituted a formidable challenge. Through this work we want to share our hands-on experience of data collection & dissemination at Crisis Management Cell. We aim to inform our readers about the important points that need to be taken into account when establishing disease surveillance centers. As per our experience, these include an assessment of demand for near-real-time data, data handlers, data architecture, data security, data quality, data record, data velocity, data variety, data variability, data documentation, data reconciliation and reflection.